Wzrost roli transakcji barterowych w handlu Wschód — Zachód - Jankowiak, Ludwik (Wydział Prawa i Administracji UAM, 1976)
The author dwells on the causes of the growling importance of bilateral barter agreements in East-Wiest tirade. To the principle clauses in the development of barter trade belong: the economic recession in the capitalist countries the rampant inflation in the western world and last but mot least the depreciation of western currencies. The said factors reawakened interest in barter transactions. The bilateral barter arrangements, of course, have always been broadly practised in trade transactions between socialist countries and in trade relations of the latter with Third World countries. The paper contains a few examples of the numerous barter arrangements with western countries. The author next proceeds to describe and analyse the main types of barter deals, that is to say clearing, switch operations, compensatiom and buy back barter. Finally, tine author drawls attention to the fact, that barter arrangements are being not only commonly used in foreign trade but also — as the American practice shows it — in purely internal trade transactions. The big concerns are switching to barter in order to secure for themselves regular and big supplies of rare raw materials and semi-finished goods, thus depriving small and medium enterprises access to needed vital supplies.
The Growing Role of the Barter Transactions in the East — West Trade